Сущность философии и ее отличие от других форм мировоззрения - Рассоха, И.Н. (Культура народов Причерноморья, 2013)
Обосновано следующее определение философии как особой профессиональной сферы
культуры: Философия есть (1) мировоззрение, т. е. общие представления о мире и человеке, (2)
выработанное самостоятельно и лично от своего имени, (3) изложенное в понятийно-логической
форме, (4) с целью обучения ему других людей, и (5) многим людям интересное. Обгрунтовано таке визначення філософії як особливої професійної сфери культури:
Філософія є (1) світогляд, тобто загальні уявлення про світ і людину, (2) вироблене самостійно і
особисто від свого імені, (3) викладене в понятійно-логічної формі , (4) з метою навчання йому інших
людей, і (5) багатьом людям цікаве. The definition of philosophy as any human world is in need of clarification. The worldview is the
closest to the philosophy more general concept. Consistency and rationalization - the main species differences
that define philosophy. Philosophy as such begins when there are original author's philosophical teachings.
Philosopher - a man whose main benefit other people occupation is teaching others in their outlook. The
following definition is justified philosophy as a special professional field of culture: philosophy is (1) worldview,
ie, general ideas about man and the world, (2) worked out by somebody on their own and in person on his
behalf, (3) as set out in the conceptual and logical form and (4) aimed to train it to others, and (5) interesting for
many people. Thereby eliminated all at once impersonal records of traditional mythological texts, as well as all
the founders of religions and the prophets (eg, Muhammad), and many mystics: their worldview received by
them as a finished product from outside, for example, directly from God.